1997
DOI: 10.1021/bc970017f
|View full text |Cite
|
Sign up to set email alerts
|

A 15-Base Acridine-Conjugated Oligodeoxynucleotide Forms Triplex DNA with Its IL-2Rα Promoter Target with Greatly Improved Avidity

Abstract: Attachment of 6,9-diamino-2-methoxyacridine to the 5' end of a purine-rich oligodeoxynucleotide targeting a 15 bp oligopurine oligopyrimidine stretch in the promoter region of the interleukin-2 receptor alpha chain (IL-2R alpha) gene results in an approximately 500-fold increase in its triplex forming avidity as determined by both band shift assay and DMS footprinting (Kd lowered from 2.5 microM to 5 nM). This oligonucleotide participates in Mg(2+)-dependent three-stranded DNA formation in which it is oriented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…Attachment to the 5'-end has a greater effect than at the 3'-end [130,134], possibly reflecting a structural difference between the 5'-and 3'-triplex-duplex junctions, since the junction at the 5'-end of the third strand is thought to present a strong intercalation site [135,136]. Most of these studies have used parallel, pyrimidine-containing oligonucleotides, though they have also been used to stabilise antiparallel GA and GT-containing triplexes [92,[137][138][139][140] as well as alternate strand triplexes containing both parallel and antiparallel motifs [141]. Attachment generally increases triplex stability by at least 100-fold, though the interaction with related non-cognate sequences is also increased [133].…”
Section: Intercalatorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Attachment to the 5'-end has a greater effect than at the 3'-end [130,134], possibly reflecting a structural difference between the 5'-and 3'-triplex-duplex junctions, since the junction at the 5'-end of the third strand is thought to present a strong intercalation site [135,136]. Most of these studies have used parallel, pyrimidine-containing oligonucleotides, though they have also been used to stabilise antiparallel GA and GT-containing triplexes [92,[137][138][139][140] as well as alternate strand triplexes containing both parallel and antiparallel motifs [141]. Attachment generally increases triplex stability by at least 100-fold, though the interaction with related non-cognate sequences is also increased [133].…”
Section: Intercalatorsmentioning
confidence: 99%
“…Attachment generally increases triplex stability by at least 100-fold, though the interaction with related non-cognate sequences is also increased [133]. However attachment of the acridine does not seem substantially to compromise the sequence specificity of binding [139]. At secondary sites where more than one binding Triplex-binding ligands have also been used for increasing the strength of binding to sites which contain pyrimidine interruptions.…”
Section: Intercalatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Clearly, then, knowledge of the kind of distortions induced by base triplet nonisomorphism would be important in enabling better design of modified bases such as to nullify the D effects (Dt8 and Dr A ) that will optimize/ minimize the destabilizing (mechanistic) effects of base triplet nonisomorphism so as to pave the way for improved stability of the triplex formed. Also, knowledge of the structural details of the grooves of the GA triplex portrayed here may facilitate the design of better ligands 63,64 specific for either the CH or the WH groove of the triplex to enhance the stability of the GA triplex. Thus, structural information of DNA triplexes comprising nonisomorphic base triplets such as reported here would be beneficial in the efficient design of TFOs to regulate gene expression as well as to induce sequence-specific distortions in a target DNA duplex.…”
Section: Discussionmentioning
confidence: 99%
“…19) Molecules with non-selective stabilizing effects would represent a powerful tool to promote triplex formation. 20,21) Among these molecules, twisted intercalating nucleic acids (TINA) have been shown to enhance the stability of triplex formation. 22) Our group previously showed that TFOs containing artificial nucleoside analogues, WNA-Et-T, exerted stabilizing effects on all four base pairs (GC, AT, CG and TA base pairs).…”
mentioning
confidence: 99%